Growth performance and Biomass estimation of Cassavaon two different Soil types - Farah Liyana Rosli (2016)
Cassava in a scientiﬁc name is called Manihot esculenta Crantz that are mainly cultivated in the tropic and sub-tropic regions of the world. It can be categorized as an important food source for diets and the third largest carbohydrate source in tropical regions after paddy and corn. The objectives in this study are to identify the suitable soil types either loam soil or Beach Ridges Interspersed with Swales (BRIS) for the planting of cassava. The problem statement is the limited agricultural lands that are suitable for the planting of cassava. Soil analysis were conducted in order to determine the soil pH level and the temperature of the soil by using the soil survey instruments for both soil types which are loam and BRIS soil. Statistical analyses also were used for growth performance—using the T-test. For biomass estimation, the sample was dried in an oven with 60 “C until constant weight. The result showed that the sample for growth performance in loam soil is higher than the sample in BRIS soil where the mean for loam soil and BRIS soil are 14.92 cm and 13.63 cm. 66 % samples survived in loam soil while, only 34 % samples survived in BRIS soil. Loam soil showed the ability of high in nutrient content for the cassava to grow well compared to the BRIS soil which is a low in nutrient content. Bris sample has higher biomass estimation which is 32.5 g than the sample in loam soil 33.05 g. That means, cassava also can grow in BRIS soil even though BRIS soil was categorized as a problematic soil. The carbon content also was determined in order to know the carbon content in the sample. The means, value for the carbon content in both soil types is higher in stem part which is 26.53g compared to other parts such as leaf part which is 10.31 g and root part which is 12.36g. It can be conclude that the growth performance of cassava is higher in loam soil which is 14.92 cm than BRIS soil which is 13.63 cm. As a conclusion, the loam soils are suitable for the planting of cassava since it showed a good result in growth performance. Furthermore, the BRIS soil has the ability to be a as a suitable candidate for the bio energy product and it can also upgrading the yield of cassava production.